Integrin α4β1/VCAM-1 Interaction Evokes Dynamic Cell Aggregation Between Immune Cells and Human Lung Microvascular Endothelial Cells at Infectious Hemolysis - Lou, Hai-Yan; Yan, Hai-Peng; Yang, Long-Gui; Fan, Jiang-hua; Cho, William C.; Xiao, Zheng-hui; Li, Shuang-Jie (Frontiers in Pharmacology, 2021)
Bacterial and viral infection is a common cause of pneumonia, respiratory failure, and even acute respiratory distress syndrome. Increasing evidence indicates that red blood cells (RBCs) may contribute to immune response and inflammation. However, the precise molecular mechanisms that link RBC and hemolysis to the development and progression of inflammatory pathologies are not entirely understood. In this study, we used bacterial endotoxin, lipopolysaccharide (LPS), to mimic an infectious hemolysis and found that RBCs dynamically regulated cell aggregation between immune cells and human lung microvascular endothelial cells (HLMVEC). When RBCs were treated with LPS, integrin α4β1 was increased and was accompanied by cytokines and chemokines release (TNF-α, IL-1β, IL-6, IL-8, IFN-γ, CXCL12, CCL5, CCL7 and CCL4). Upon α4β1 elevation, RBCs not only facilitated mature monocyte derived dendritic cell (mo-DCs) adhesion but also promoted HLMVEC aggregation. Furthermore, co-culture of the supernatant of LPS pre-treated RBCs with mo-DCs could promote naïve CD4 T cell proliferation. Notably, the filtered culture from LPS-lysed RBCs further promoted mo-DCs migration in a concentration dependent manner. From a therapeutic perspective, cyclic peptide inhibitor of integrin α4β1 combined with methylprednisolone (α4β1/Methrol) remarkably blocked RBCs aggregation to mo-DCs, HLMVEC, or mo-DCs and HLMVEC mixture. Moreover, α4β1/Methrol dramatically reduced mo-DCs migration up-regulated glucocorticoid-induced leucine zipper in mo-DCs, and ultimately reversed immune cell dysfunction induced by hemolysis. Taken together, these results indicate that integrin α4β1 on RBCs could mediate cell-cell interaction for adaptive immunity through influencing cell adhesion, migration, and T cell proliferation.